2021
DOI: 10.7554/elife.61504
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater monitoring by nanopore sequencing

Abstract: While traditional microbiological freshwater tests focus on the detection of specific bacterial indicator species, including pathogens, direct tracing of all aquatic DNA through metagenomics poses a profound alternative. Yet, in situ metagenomic water surveys face substantial challenges in cost and logistics. Here, we present a simple, fast, cost-effective and remotely accessible freshwater diagnostics workflow centred around the portable nanopore sequencing technology. Using defined compositions and spatiotem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 88 publications
0
78
0
Order By: Relevance
“…Due in part to these key advantages-ease of library preparation, the small and portable footprint of ONT sequencing instruments, and the generation of real-time sequencing datananopore sequencing is particularly well-suited for the purposes of pathogen detection and biosurveillance [14,[16][17][18]. In contrast to conventional surveillance methods, which rely heavily on nucleic acid amplification (i.e., PCR), pathogen detection by nanopore sequencing can: (1) bypass the requirement that investigators possess a priori knowledge of the pathogen(s) being targeted, (2) enable detection of many agents simultaneously, and (3) provide a greater scope of downstream genomic sequence information suitable for pathogen strain typing, functional characterization, and phylogenetics [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Due in part to these key advantages-ease of library preparation, the small and portable footprint of ONT sequencing instruments, and the generation of real-time sequencing datananopore sequencing is particularly well-suited for the purposes of pathogen detection and biosurveillance [14,[16][17][18]. In contrast to conventional surveillance methods, which rely heavily on nucleic acid amplification (i.e., PCR), pathogen detection by nanopore sequencing can: (1) bypass the requirement that investigators possess a priori knowledge of the pathogen(s) being targeted, (2) enable detection of many agents simultaneously, and (3) provide a greater scope of downstream genomic sequence information suitable for pathogen strain typing, functional characterization, and phylogenetics [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…16s rDNA sequencing is based on partial similarity in the complete gene with an approximate length of 1540 bases and variety in nine hypervariable regions unique for each bacterial genus [ 127 ]. Unfortunately, the first and second generation of sequencing depend on a relatively large and stationary apparatus with high running costs [ 128 ]. This changed after the introduction of the third generation of sequencers developed by Oxford Nanopore Technology.…”
Section: Detection Of Sars-cov-2mentioning
confidence: 99%
“…Another study evaluating long-read sequencing of the 16S rRNA gene (amplicon sequencing) in water from informal settlements in Nepal found that amplicon sequencing correlated with qPCR results for detection of Vibrio cholera but recommended combined use to avoid false positives 24 . Other studies have found nanopore sequencing (metagenomic and amplicon) useful for profiling spatial and temporal variation in the core communities and function of bacteria in river samples 53,54 .…”
Section: Utility Of Assembled Long Readsmentioning
confidence: 99%